“Arreda homem, que aí vem mulher!”: as pombagiras de umbanda e o empoderamento feminino - Gomes, Raphael Fernandes (2019)
The purpose of this dissertation is to present, in the light of gender studies, a debate about the issue of female empowerment using the relationships between the sacred field in Afro-Brazilian religions, through the figure of entities called Pombagiras and people who attend the religious spaces where these entities manifest themselves, be they consulters or mediums. The study set out to analyze and understand how the behavior, advice and discourse of these entities influence the life of their consultants and also of their mediums, encouraging them to free themselves from circumstances where they are confronted with the implications of being inserted in a a society based on male ideals, of patriarchal origin and derived from religious dogmas established by Western culture, more specifically the Judeo-Christian religions and the Greek myths that denote a huge subalternization of women, their objectification and, according to them, a tendency to evil and sin, evidenced by the practices adopted during the Inquisition. The contrast between these cultures and the Afro-Brazilian culture, in the feminine aspect, is carried out through a narrative that consolidates the practices and myths inherent to these religions, highlighting the important role that women, “mães de santo”, Orixás and entities, in the terreiros. In this context, the Pombagiras figure is presented as an element of building the empowerment of women who have contact with them. Through the narratives presented in the field research, it is possible to perceive that the Pombagiras make their consultants and mediums in women psychic conscious and empowered. Methodologically the work is based on extensive bibliographical research and qualitative field research, analyzed through thematic analysis according to the foundations established by Laurence Bardin and an epistemological view based on the epistemology of the macumbas of Luiz Antônio Simas and Luiz Rufino.